Enzymes involved in the biosynthesis of the very-long-chain polyunsaturated fatty acids of rat spermatogenic cell sphingolipids - Santiago Valtierra, Florencia Ximena (2017)
The sphingolipids (SL) of rodent germ cells contain very-long- chain polyunsaturated fatty acids (V), in nonhydroxy (n-V) and 2-hy- droxy (h-V) forms, whose biosynthesis requires the expression of several elongases (Elovl) and a fatty acid 2-hydroxylase (Fa2h). Our objective was to characterize the expression of these enzymes as a function of postnatal development and germ cell differentiation. We employed qPCR for mRNA levels, Western blot and immunofluo- rescence for protein expression, and [3 H]-labeled precursors for en- zyme activity. Elovl4, involved in C24-C34 fatty acid biosynthesis, was expressed at the mRNA, but not at the protein level, at early prepu- beral ages. Such mRNA was a product of Sertoli cells. Elovl4 mRNA and protein were both produced by germ cells. In agreement with the relative abundance of n-V in their SL, the Elovl4 enzymatic ac- tivity was higher in the premeiotic pachytene spermatocytes than in postmeiotic round and late spermatids (p<0.05), and was negligible in Sertoli cells. By contrast to Elovl4 mRNA, that of Fa2h was absent from Sertoli cells and from prepuberal testes (p<0.05). Fa2h mRNA and protein were detectable only in concomitance with the appear- ance of spermatids, the sperm precursors whose SL are the richest in h-V. Consistently, selective depletion of germ (but not Sertoli) cells from adult rat testes by exposures to mild hyperthermia reduced the mRNA levels of Fa2h to a much larger extent (p<0.001) than that of Elovl4. Among germ cells of adult testes, Elovl4 protein content was high in spermatocytes and late spermatids, while Fa2h was mostly expressed in the latter, residual bodies and spermatozoa. By using inhibitors of specific steps of the SL biosynthetic route, germ cells in culture showed ability to de novo synthesize SL containing n-V and h-V. Our results underscore the presence of a developmentally programmed and a cell-specific regulation of the Elovl4 and Fa2h expression and activity as germ cell differentiation proceeds.